Prevalence and Outcome of Admission of Preterm Neonates: A Hospital Based Study at the Tertiary Care Center in Rural Nepal - Shrestha, Sandeep; Sindan, Namrata; Kayastha, Nirajana; Thani, Kamal Prasad; Jha, Khushbu; Pahadi, Nirmala; Shrestha, Annie (Journal of Karnali Academy of Health Sciences, 2021)
Background: Preterm births are one of the leading causes of perinatal mortality and morbidity despite of recent advances. It causes long-term medical problem for affected children, the financial burden for their families as well as the health care system of country. The objective and aim of the present study was to identify prevalence and outcome of preterm admissions attending a tertiary care centre in rural Nepal, Jumla. Methods: A retrospective study was carried out on 52 preterm births which were admitted at the Neonatal Intensive Care Unit (NICU) and Special Newborn Care Unit (SNCU) of the Karnali Academy of Health Sciences (KAHS), Jumla from January 2020 to December 2020. This study was carried out from March 2021 to July 2021 for 5 months. All the data were recorded and then analyzed using Statistical Package for Social Sciences (SPSS) version 16. P-value <0.05 was considered statistically significant. Results: Preterm admissions constituted 19.4% of all admissions i.e 52 out of 268 cases at the NICU of KAHS. The mean birth weight and mean gestational age were 1730 ± 378 grams and 33.3 ± 2.13 weeks respectively. The most common cause for hospital admission was sepsis (34.62 %) followed by perinatal asphyxia (15.39%) and neonatal jaundice (13.47%). Premature rupture of membrane (28.8%) was the most common risk factor of preterm delivery followed by hypertensive disorders of pregnancy (15.3%) and teenage pregnancy (11.5%) in our study. Mortality was observed in 10 (19.2%) cases. Conclusion: Prematurity is still one of the important and main cause for admissions in intensive care unit. Identification of at risk pregnancy, early detection and treatment of medical diseases, improving pregnant women’s health care quality may decrease the rate of preterm birth.